Springback analysis in sheet metal forming using modified ludwik stress-strain relation - Patel S.K.; Lal R.K.; Dwivedi J.P.; Singh V.P. (My University, 2025)
This paper deals with the springback analysis in sheet metal forming using modified Ludwik stress-strain relation. Using the deformation theory of plasticity, formulation of the problem and spring back ratio is derived using modified Ludwik stress strain relationship with Tresca and von Mises yielding criteraia. The results have been representing the effect of different value of Y/E or σo/E ratio, different values of Strain hardening index (n), Poisson's ratio (), and thickness on spring back ratio (Ro/Rf). The main aim of this paper is to study the effects of the thickness, Y/E ratio, n and Poisson's ratio in spring back ratio. © 2013 Sanjay Kumar Patel et al.